Positive predictive value of the prostate imaging reporting and data system combined with single related indicators in prostate cancer across different prostate zones - Shen, XiaFeng; Yang, LuYao; Wang, ShiWei; Shen, JianLiang (Frontiers in Oncology, 2026)
IntroductionThis study aimed to evaluate the positive predictive value (PPV) of the Prostate Imaging Reporting and Data System (PI-RADS) combined with single related indicators in diagnosing prostate cancer (PCa) across different prostate zones.MethodsPatients with complete clinical data who underwent prostate magnetic resonance imaging from January 2019 to October 2024 were retrospectively analyzed. PI-RADS was used for diagnosis, zoning, and grading, with 533 cases scoring ≥3. PPVs for PCa across different prostate zones were calculated by combining age, prostate-specific antigen (PSA), PSA density (PSAd), and prostate volume. Differences between non-PCa and PCa groups were compared using independent sample t- and rank-sum tests. Diagnostic efficacy was assessed using area under the curve (AUC) values for receiver operating characteristic curves. Univariate logistic regression analysis was used to identify factors associated with malignant pathology.ResultsThe PPV for PI-RADS scores 3–5 was 20.6% (33/160), 61.1% (159/260), and 80.5% (91/113), respectively. PPVs for PCa across peripheral, transitional, and multi-zones were 78.6% (96/122), 35.2% (114/323), and 82.9% (73/88), respectively. Age, PSA, PSAd, and prostate volume significantly differed between the non-PCa and PCa groups, with AUC values of 0.629, 0.709, 0.809, and 0.703, respectively, and were significantly associated with malignant pathology (P< 0.001, univariate logistic regression analysis).ConclusionCombining the PI-RADS with other clinical indicators effectively enhanced its initially low PPV for transitional zone lesions, particularly when the PSAd was ≥0.15 ng/mL2 or the PSA was >10 ng/mL.